Timing of ergogenic aids and micronutrients on muscle and exercise performance - Stecker, R. A.; Harty, P. S.; Jagim, A. R.; Candow, D. G.; Kerksick, C. M. (Journal of the International Society of Sports Nutrition, 2019)
The timing of macronutrient ingestion in relation to exercise is a purported strategy to augment muscle accretion, muscle and athletic performance, and recovery. To date, the majority of macronutrient nutrient timing research has focused on carbohydrate and protein intake. However, emerging research suggests that the strategic ingestion of various ergogenic aids and micronutrients may also have beneficial effects. Therefore, the purpose of this narrative review is to critically evaluate and summarize the available literature examining the timing of ergogenic aids (caffeine, creatine, nitrates, sodium bicarbonate, beta-alanine) and micronutrients (iron, calcium) on muscle adaptations and exercise performance. In summary, preliminary data is available to indicate the timing of caffeine, nitrates, and creatine monohydrate may impact outcomes such as exercise performance, strength gains and other exercise training adaptations. Furthermore, data is available to suggest that timing the administration of beta-alanine and sodium bicarbonate may help to minimize known untoward adverse events while maintaining potential ergogenic outcomes. Finally, limited data indicates that timed ingestion of calcium and iron may help with the uptake and metabolism of these nutrients. While encouraging, much more research is needed to better understand how timed administration of these nutrients and others may impact performance, health, or other exercise training outcomes.